Mixing Medicines The Global Drug Trade and Early Modern Russia - Griffin, Clare (Intoxicating histories, 2022)
Early modern Russians preferred one method of treating the sick above all others: prescribing drugs. The Moscow court sourced pharmaceuticals from Asia, Africa, Western Europe, and the Americas, in addition to its own sprawling empire, to heal its ailing tsars. Mixing Medicines explores the dynamic and complex world of early modern Russian medical drugs, from its enthusiasm for newly imported American botanicals to its disgust at Western European medicines made from human corpses. Clare Griffin draws from detailed apothecary records to shed light on the early modern Russian Empire's role in the global trade in medical drugs. Chapters follow the trade and use of medical ingredients through networks that linked Moscow to Western Europe, Asia, and the Americas; the transformation of natural objects, such as botanicals and chemicals, into medicines; the documentation and translation of medical knowledge; and Western European influence on Russian medical practices. Looking beyond practitioners, texts, and ideas to consider how materials of medicine were used by one of the early modern world's major empires provides a novel account of the global history of early modern medicine. Mixing Medicines offers unique insight into how the dramatic reshaping of global trade touched the day-to-day lives of the people living in early modern Russia.